Design and Simulation of a New Type of Stair Climbing Wheelchair based on Recur Dyn - Chen Weirong; Zhang Hua; Wang Feiwen; Zheng Min; Liu Cheng (Jixie chuandong)
The stair climbing wheelchair is mainly used to assist vulnerable groups to achieve stair climbing process,so its reliability and stationarity is particularly important. By adopting composite stair climbing wheelchair structure,a new crawler chassis which overcomes the problems existing in the traditional crawler structure ladder climbing process is designed. Under the environment of the Track LM module of RecurDyn,the repeated simulation and modification of the climbing process of the designed wheelchair are carried out. Finally,a modified dynamic simulation process is obtained,and the driving torque,the vibration displacement and the acceleration curve of the center of gravity in vertical direction are extracted. The realization of the simulation process has important guiding significance for the type selection and assembly of a new type of physical prototype of the staircase wheelchair.